Public Management as a Design-Oriented Professional Discipline - Michael Barzelay (Edward Elgar Publishing, 2019)
While public management has become widely spoken of, its identity and character is not well-defined. Such disparity is an underlying problem in developing public management within academia, and in the eyes of practitioners. In this book, Michael Barzelay tackles the challenge of making public management into a true professional discipline. Barzelay argues that public management needs to integrate contrasting conceptions of professional practice. By pressing forward an expansive idea of design in public management, Barzelay formulates a fresh vision of public management in practice and outlines its implications for research, curriculum development and disciplinary identity.